2016
DOI: 10.1115/1.4034678
|View full text |Cite
|
Sign up to set email alerts
|

A Nonclassical Finite Element Approach for the Nonlinear Analysis of Micropolar Plates

Abstract: Based on the micropolar elasticity theory, a size-dependent rectangular element is proposed in this article to investigate the nonlinear mechanical behavior of plates. To this end, a novel three-dimensional formulation for the micropolar theory with the capability of being used easily in the finite element approach is developed first. Afterward, in order to study the micropolar plates, the obtained general formulation is reduced to that based on the Mindlin plate theory. Accordingly, a rectangular plate elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…For web-core beams this was done in (Karttunen et al, 2019) and for full 3-D web-core panels this will be carried out in future studies. Finally, this study introduced a theoretical micropolar plate model which can be used as the basis for micropolar finite element developments similar to those presented by Ansari et al (2017bAnsari et al ( , 2018. Furthermore, the micromorphic continuum theory may provide a suitable framework for modeling local buckling and vibrations of lattice core sandwich panels through its additional degrees of freedom (Eringen, 2012;Isbuga and Regueiro, 2011;Ansari et al, 2016Ansari et al, , 2017a.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For web-core beams this was done in (Karttunen et al, 2019) and for full 3-D web-core panels this will be carried out in future studies. Finally, this study introduced a theoretical micropolar plate model which can be used as the basis for micropolar finite element developments similar to those presented by Ansari et al (2017bAnsari et al ( , 2018. Furthermore, the micromorphic continuum theory may provide a suitable framework for modeling local buckling and vibrations of lattice core sandwich panels through its additional degrees of freedom (Eringen, 2012;Isbuga and Regueiro, 2011;Ansari et al, 2016Ansari et al, , 2017a.…”
Section: Discussionmentioning
confidence: 98%
“…The works of Eringen (2012), Altenbach and Eremeyev (2009) and Altenbach et al (2010) discuss the key theoretical aspects of micropolar plate theories and the literature reviews therein encompass a lengthy period of research on such plates. Of the more recent papers on micropolar plates we mention those of Kvasov and Steinberg (2013); Sargsyan and Sargsyan (2014); Abadikhah and Folkow (2015); Ansari et al (2017b) and Zozulya (2018). However, the aforementioned models are not applicable in the present context as their constitutive equations do not address any particular microstructure such as a webcore.…”
Section: Unit Cellmentioning
confidence: 99%
“…More on this relation can be found. Detailed study comparing the classical and micropolar theory can be found in the work of Ansari et al [28].…”
Section: Resultsmentioning
confidence: 99%
“…Kvasov and Steinberg (2013) presented finite element model for the bending analysis of micropolar elastic plates. Godio et al (2015) proposed a displacement-based finite element model for micropolar plates, Ansari et al (2017) proposed a nonlinear finite element model for micropolar plates where the nonlinear micropolar strains were considered. Ansari et al (2018) used 3-D micropolar elements to study the vibrations of micro-beams and micro-plates.…”
Section: Introductionmentioning
confidence: 99%